Applications and regulatory of nanotechnology‐based innovative in vitro diagnostics. Issue 2 (8th December 2020) - Chen, Kuan; Han, Houyu; Tuguntaev, Ruslan G.; Wang, Peirong; Guo, Weisheng; Huang, Jiayu; Gong, Xiaoqun; Liang, Xing‐Jie
Abstract: Nanotechnology‐based in vitro diagnostics (nanoIVDs) are widely studied for disease diagnostics with promising sensitivity, specificity, and convenience. However, it is still a major challenge for both regulatory authorities and scientific researchers to accelerate the clinical translation of such an innovative technology. Herein, this perspective discussed the benefits and challenges of nanoIVDs as well as the administration considerations on the distinguish features of nanoIVDs by regulatory authorities, so as to further achieve the evaluation, translation, and application of nanoIVD products. Abstract : The common efforts of regulatory science and scientific research devoting to NanoIVDs application.